Comparison between cuff-based and invasive systolic blood pressure amplification. Issue 10 (23rd October 2022) - Bui, Tan V.; Picone, Dean S.; Schultz, Martin G.; Armstrong, Matthew K.; Peng, Xiaoqing; Black, J. Andrew; Dwyer, Nathan; Roberts-Thomson, Philip; Adams, Heath; Hughes, Alun D.; Sharman, James E.
Abstract : Objective: Accurate measurement of central blood pressure (BP) using upper arm cuff-based methods is associated with several factors, including determining the level of systolic BP (SBP) amplification. This study aimed to determine the agreement between cuff-based and invasively measured SBP amplification. Methods: Patients undergoing coronary angiography had invasive SBP amplification (brachial SBP – central SBP) measured simultaneously with cuff-based SBP amplification using a commercially available central BP device (device 1: Sphygmocor Xcel; n = 171, 70% men, 60 ± 10 years) and a now superseded model of a central BP device (device 2: Uscom BP+; n = 52, 83% men, 62 ± 10 years). Results: Mean difference (±2SD, limits of agreement) between cuff-based and invasive SBP amplification was 4 mmHg (−12, +20 mmHg, P < 0.001) for device 1 and −2 mmHg (−14, +10 mmHg, P = 0.10) for device 2. Both devices systematically overestimated SBP amplification at lower levels and underestimated at higher levels of invasive SBP amplification, but with stronger bias for device 1 ( r = −0.68 vs. r = −0.52; Z = 2.72; P = 0.008). Concordance of cuff-based and invasive SBP amplification across quartiles of invasive SBP amplification was low, particularly in the lowest and highest quartiles. The root mean square errors from regression between cuff-based central SBP and brachial SBP were significantly lower (indicating less variability) than from invasive regression models ( P < 0.001). Conclusions: Irrespective of the difference from invasive measurements, cuff-based estimates of SBP amplification showed evidence of proportional systematic bias and had less individual variability. These observations could provide insights on how to improve the performance of cuff-based central BP.